Public Administration Reform in Romania: Assessing the Past and Looking into the Future - Constantin Marius Profiroiu; Ionuț Ciprian Negoiță (Transylvanian Review of Administrative Sciences, 2022)
This article provides an account of the transformational capacity of Romanian public administration in relation to four main aspects: (1) human resource performance and integrity; (2) territorial, functional and institutional decentralization; (3) public policies and (4) capitalizing on the digital and innovative component. The Romania case study highlights the gradual transformation of public administration in the last 30 years, as a reaction to the emergence of economic, social and political crises. For an imperative and irreversible change, we have identified directions for capitalizing on opportunities and good practices in the matter, in the context of the intensified integration process in NATO and the EU. We have analyzed the strategic documents on strengthening and accelerating the transformation of public administration and highlighted the need for the interconnection and interdependence of its four pillars to meet the specific objectives of Horizon 2030. For decision-makers, practitioners and researchers, this article aims to stimulate and contribute to the dedicated public debate and consultation of coherent, predictable and sustainable legislation and practices in the matter.